ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS DALAM MENYELESAIKAN MASALAH POKOK BAHASAN BANGUN DATAR SEGI EMPAT DITINJAU DARI KECERDASAN EMOSIONAL SISWA KELAS VIII-D SMP NEGERI 1 SUMBERMALANG - Laksananti, Putri Meilinda; Setiawan, Toto' Bara; Setiawani, Susi (Department of Mathematics Education , University of Jember, 2017)
Abstract. Mathematical communication is the ability to reflect the understanding of mathematics in various forms whether it is oral, in the form of pictures, graphs and others. The indicators of mathematical communication ability used in this research are to understand the mathematical idea of ​​the problem given in written and oral form, to change the given problem into visual form, to reveal the strategy in solving the problem, to solve the problem using the strategy, to interpret the mathematical information in the different math representation. This study aims to analyze the ability of mathematical communication in solving the problem of quadrilateral topic in terms of students’ emotional intelligence of VIII-D in SMP Negeri 1 Sumbermalang. The type of this research is descriptive qualitative research with the subject of 6 students from VIII-D of SMP Negeri 1 Sumbermalang selected based on students' emotional intelligence. Methods of data collection in this study were questionnaires, written tests and oral tests. The results of analysis of student's mathematical communication ability based on emotional intelligence are found that students with higher emotional intelligence have better communication skill of math. Keywords: Mathematical communication, emotional intelligence, quadrilaterals.